Forestry Planning and Changing Concepts of Management - Prasad, Dayal (Indian Forester, 1976)
Forestry planning in India has seldom received adequate attention therefore supply/demand problems had long been accumulating. Whereas, natural forests of the country are depleting fast due to unsystematic fellings and inadequate replenishments, the demand for forest based products is steadily increasing. Annual consumption of industrial wood is expected to reach 50 million m3 by 1988-89. The existing slow grown forests with traditional conservatory management are apparently incapable of abridging the widening demand/supply gap. The challenge of meeting the projected demands can only be met amicably by adequate planning based on the dynamic concept of aggressive management followed with efficient implementation, sufficient fund allocation and creation of necessary organ for undertaking developlmental activities. Enormousity of financial and executive implications necessitate sharing of activities with industries and establishment of a separate forest ministry or autonomous central organisation.